Quantification of the competition load of the sets in high-level volleyball in the year 2021 - Lopez Martinez, E.; Garcia, G. M. G.; Molina-Martin, J. J. (Journal of Physical Education and Sport, 2023)
Many different factors can affect the performance of athletes in competitions and condition the analysis of technical and tactical performance. One of these factors is the so-called competition load of the set, understood as the difference in points at the end of the set. The main objective of the present study was to investigate the competition load of volleyball sets, to establish reference values that will allow classifying the sets as balanced or unbalanced for the male and female categories. A total of 2368 sets were collected from the main international volleyball team competitions in 2021, for a total of 1357 male sets, and 1011 female sets. A K-means clustering analysis was performed, allowing the classification of the sets as balanced when the difference was =6 for the male category, and =7 for the female one; and unbalanced when these values were higher. To study how the rest of the variables analyzed affected the percentage of balanced and unbalances sets, a Pearson`s chi-square (x2) analysis was performed, obtaining significant differences on the percentage of balanced and unbalanced sets as a function of the number of sets in the game in both categories. In the female category, the variable of competition analyzed also showed significant differences. Lastly, a CHAID analysis showed that the variable number of sets per game was the main predictor variable for classifying the sets, allowing for the correct classification of 60.4% of the sets in the male category, and 62.7% in the female one. In conclusion, the competition load was associated with the total number of sets per match and the tie-breaker set; and it was only related with the competition analyzed in the female category. The competition load was not significantly related with the competition phase analyzed in any of the two categories. These results can be taken into account by coaches in order to study how the balance in the sets affects the performance of technical indicators, and the variability in the systems or game strategies.